Biochemical Composition of Propolis and Its Efficacy in Maintaining Postharvest Storability of Fresh Fruits and Vegetables - İbrahim Kahramanoğlu; Volkan Okatan; Chunpeng Wan (Journal of Food Quality)
Propolis, also called “bee-glue,” is a natural resinous substance produced by honeybees from plant exudates, beeswax, and bee secretions in order to defend the hives. It has numerous phenolic compounds with more than 250 identified chemical compounds in its composition, which are also known to significantly vary according to the plant sources and season. Moreover, it has a long history in the traditional and scientific medicine as having antibacterial, anticancer, anti-inflammatory, anti-infective, and wound healing effects since 300 BC. In addition to its nutritional and health-promoting effects, it has been reported to improve the postharvest storability of fresh fruits, vegetables, and processed food products. Herein, the biochemical composition and the efficacy of propolis in maintaining the postharvest storability of fresh food products were discussed to provide comprehensive guide to farmers and food processing and storage sectors and to scientists. This review paper also highlights the important points to which special attention should be given in further studies in order to be able to use propolis to develop biopreservatives industrially and for quality preservation during storage.